2004
DOI: 10.1086/425615
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Community‐Acquired Pneumonia in Seniors: Results of a Population‐Based Study

Abstract: On the basis of these data, we estimate that roughly 915,900 cases of community-acquired pneumonia occur annually among seniors in the United States and that approximately 1 of every 20 persons aged >or=85 years will have a new episode of community-acquired pneumonia each year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
347
1
27

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(394 citation statements)
references
References 19 publications
(20 reference statements)
19
347
1
27
Order By: Relevance
“…Many workingage adults with influenza do not present for medical attention although they may still incur absenteeism and productivity losses [1,39]. Previous studies have suggested that patients with diabetes who experience infectious diseases may be more likely to present for medical attention and to be hospitalised [40,41], and this may lead to overestimates of influenza-attributable illness specifically in diabetic adults. Because increased medical attention likely applies generally, regardless of infectious aetiology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Many workingage adults with influenza do not present for medical attention although they may still incur absenteeism and productivity losses [1,39]. Previous studies have suggested that patients with diabetes who experience infectious diseases may be more likely to present for medical attention and to be hospitalised [40,41], and this may lead to overestimates of influenza-attributable illness specifically in diabetic adults. Because increased medical attention likely applies generally, regardless of infectious aetiology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…From the cost study performed in Sao Paulo State, Jackson et al 5 in 2004, 12.5% of the patients over 80 years-old admitted to hospital for pneumonia die while in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…4 In USA, pneumonia rates for individuals between 65 and 69 years old were ª 2015 John Wiley & Sons Ltd, Immunology, 146, 100-112 18Á2/1000 person-years and 52Á3/1000 person-years for individuals over 85 years of age. 5 S. pneumoniae contains several virulence factors used to evade the immune response at different stages of infection. [6][7][8] For instance, this bacterium is able to prevent phagocytosis and complement binding, induce necrosis of immune cells and cleavage of IgA antibodies.…”
Section: Introductionmentioning
confidence: 99%